[Crisis in the Gulf; War of the widows; A taste of Tinio's "La Travista" - Aquino, Corazon Cojuangco 1933- .; Marcos, Imelda Romualdez 1929- .; Lazaro, Cheche (The Probe Team, 1990)
Interviews with Filipino overseas contract workers in Kuwait on their experience going back due to the gulf war; Political rivalry between President Corazon Aquino and former first lady Imelda Marcos; Philipine version of an Italian opera directed by Rolando Tinio.